2008
DOI: 10.2193/2007-035
|View full text |Cite
|
Sign up to set email alerts
|

Social Indices of Breeding Productivity in Parkland Mallards

Abstract: Social indices were developed to assess breeding productivity of waterfowl based on weekly roadside surveys of social groupings (i.e., pairs, lone M, flocked M). We calculated social indices for mallard (Anas platyrhynchos) populations breeding on 16 study sites in the Canadian parklands from 1993 to 1998 using 7 previously developed indices. We also calculated duckling:pair ratios from our roadside counts, and we obtained independent measures of nesting effort, nesting success, female success, and fledging ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
(42 reference statements)
1
5
0
Order By: Relevance
“…We conducted ground‐based surveys (Dzubin , Hammond ) to estimate mallard breeding‐pair density during late April and early May on 6 randomly chosen, non‐overlapping 2.6‐km 2 (8,050 m × 320 m) strip transects within the study area. We attempted to schedule pair counts when roadside pair surveys (Arnold et al ) revealed approximately a 1:1 ratio of paired to unpaired males (Wishart ). We surveyed all wetlands within transect boundaries and recorded mallards by social status (Dzubin , Wishart ).…”
Section: Methodsmentioning
confidence: 99%
“…We conducted ground‐based surveys (Dzubin , Hammond ) to estimate mallard breeding‐pair density during late April and early May on 6 randomly chosen, non‐overlapping 2.6‐km 2 (8,050 m × 320 m) strip transects within the study area. We attempted to schedule pair counts when roadside pair surveys (Arnold et al ) revealed approximately a 1:1 ratio of paired to unpaired males (Wishart ). We surveyed all wetlands within transect boundaries and recorded mallards by social status (Dzubin , Wishart ).…”
Section: Methodsmentioning
confidence: 99%
“…We obtained similar correlations between BPRs and hen success when we used unadjusted estimates of brood abundance (A. Pagano, University of Minnesota, unpublished data; see also Arnold et al ), but we do not recommend such an approach for long‐term studies that encompass a wide variety of wetland habitats. Detection probabilities for broods varied among years, and more importantly, the covariates that best predicted detection probabilities also varied among years.…”
Section: Discussionmentioning
confidence: 81%
“…In our study, SA‐BPRs explained approximately one‐third of the observed variation in hen success. Similarly, Arnold et al () found that uncorrected duckling–pair ratios explained 26% of the variation in mallard hen success and 48% of the variation in mallard nesting success estimates from 16 study sites in the Canadian Parklands. Not all of this lack of fit was necessarily due to imprecision of BPRs, because estimates of hen success are also affected by measurement error, but in our study imprecision of SA‐BPR estimates was approximately 3‐fold larger than imprecision of estimated hen success (Fig.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Thus, an increase in detection probability of grouped males, as shown by our study, would be expected as a result of this behavior. Understanding how detection differs among different indicated breeding pair criteria has important implications for breeding waterfowl survey design as indicated breeding pair criteria are used not only to accurately estimate breeding pair abundances but also as an index to waterfowl breeding success (Brasher et al 2002, Arnold et al 2008. Brasher et al (2002) suggested that indicated breeding pair criteria could lead to overestimated breeding pair abundances and underestimated production indices due to incorrectly classifying unpaired males as paired, although our study suggests potential underestimation of breeding pair abundances and overestimation of production indices by not accounting for imperfect detection of the various criteria.…”
Section: Discussionmentioning
confidence: 99%